2019
DOI: 10.2147/imcrj.s200657
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ulnar nerve palsy as a complication of closed both-bone forearm fracture in a pediatric patient: a case report</p>

Abstract: Background: Fractures of both the ulna and radius, known as both-bone forearm fractures are common among the pediatric population. However, ulnar nerve palsy is a rare complication. Nerve damage can be due to multiple factors. Identification of the type of nerve damage is vital for proper management of this complication. Here, we present a case of ulnar nerve palsy complicating a closed both-bone forearm fracture in a pediatric patient. Furthermore, we explored how to best manage such cases and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, complete anatomical reduction is preferred when surgery is performed so that nerve entrapment or nerve tethering can be avoided [3]. Surgery is also recommended when healing is delayed after conservative management, although no specific time frame is mentioned [7]. Federer et al [5] concluded that frequent follow-up evaluations (at four to six weeks) are a must, and in cases where physical examination is inconclusive of nerve function, nerve conduction studies and MRI can be used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complete anatomical reduction is preferred when surgery is performed so that nerve entrapment or nerve tethering can be avoided [3]. Surgery is also recommended when healing is delayed after conservative management, although no specific time frame is mentioned [7]. Federer et al [5] concluded that frequent follow-up evaluations (at four to six weeks) are a must, and in cases where physical examination is inconclusive of nerve function, nerve conduction studies and MRI can be used.…”
Section: Discussionmentioning
confidence: 99%